Impact of a Structured Educational Programme on the Knowledge of Antibiotic Usage and Resistance among Undergraduate Non Medical Students: A Research Protocol - Lalhmachhuani Hmar; Ruchira Ankar (Journal of Clinical and Diagnostic Research)
Introduction: One of the most widely used medications to treat infections in a variety of medical specialities is an antibiotic. While their names are well known and they are widely used, there is insufficient education in the community, especially in developing countries, regarding the appropriate administration of antibiotics, antibiotic resistance, and its effects. As the demand for antibiotics increases day by day, the need for awareness and education becomes increasingly crucial. Need of the study: Global health is seriously threatened by bacteria resistant to the drugs used to treat them. We call this resistance to antibiotics. This can lead to infections that are difficult or impossible to treat, as well as an increased risk of death and morbidity. Research on antibiotic resistance and public and healthcare provider awareness of these issues is essential to prevent Antimicrobial Resistance (AMR) and guarantee that antibiotics are used appropriately. Aim: To assess the efficacy of a structured educational intervention in raising undergraduate non medical students’ knowledge of antibiotics and their resistance. Materials and Methods: A quasi-experimental study will be conducted at the Indian state of Maharashtra’s Indraprastha New Arts Commerce and Science College, Wardha from August 2024 through December 2024. A quantitative method will be used to assess how well the structured teaching programme has affected students’ knowledge of antibiotics and their resistance. A total of 65 students will participate and a structured questionnaire will be used for data collection. The tools will consist of- Section I: Demographic data like age, gender, types of family, resident and socioeconomic status. Section II: Structured knowledge questionnaire on the knowledge of antibiotics and their resistance. Descriptive and inferential statistics will be used to classify and analyse the participant data to meet the study’s objectives. Frequency, mean, standard deviation, mean percentage, and structured questionnaires will be used to explain demographic variables. A paired t-test will be applied to ascertain the significance of the variation in the knowledge score between the pre and post-test. The Chi-square test will be applied to determine the association between the knowledge level and demographic variables.